Healthcare personnel's attitude and coverage about tetanus vaccination in Turkey: a multicenter study - Seyman, Derya; Keskin, Aysegul Seremet; Kucukates, Emine; Ceylan, Mehmet Resat; Kul, Gulnur; Tosun, Selma; Altuntas, Bulent (Taylor & Francis Inc, 2022)
The tetanus vaccine is not routinely given to Turkish adults. Protective tetanus immunity decreases with age. Health-care personnel (HCPs), who are role models in the field of health, are a target group in order to achieve a higher rate of tetanus vaccination in the community. This study was designed to evaluate attitudes and coverage regarding tetanus vaccination among a large sample of Turkish HCPs. This cross-sectional epidemiologic study was conducted from July to August 2019. A questionnaire was sent to HCPs using social media. Of the 10,644 HCPs included in the study, 65% were female. Overall, the tetanus vaccination coverage (TVC) among HCPs was 78.5% (95% CI: 77.7%-79.3%). TVC was significantly higher among physicians [83.4% (95% CI: 82%-84.6%); p < .001] compared with all other HCPs except nurses. Older age (>= 40 years) and length of professional experience were significantly correlated with TVC. Of the 8353 HCPs who received tetanus vaccines during their lifetime, 73.03% received tetanus vaccination in the past 10 years. The self-vaccination rate for protection against tetanus was 13.1%. Acute injuries (25.42%) and pregnancy (23.9%) were the most common reasons for having the tetanus vaccine. One-third (33.7%) of HCPs did not have information about whether pregnant women could receive tetanus vaccinations. This survey study provided excellent baseline information about HCPs' coverage rates and attitudes regarding tetanus vaccination. The present results suggested that tetanus boosters for HCPs should be established as soon as possible, and revealed that the HCPs younger than 30 years with relatively less professional experience and all other HCPs except nurses and physicians should be identified as the target population for future intervention programs.
Keywords: Tetanus vaccination; healthcare personnel; coverage; attitude; questionnaire